2022
DOI: 10.3389/fnagi.2022.900523
|View full text |Cite|
|
Sign up to set email alerts
|

Gender-specific prevalence and risk factors of mild cognitive impairment among older adults in Chongming, Shanghai, China

Abstract: ObjectiveThis study explores the gender differences in the prevalence of mild cognitive impairment (MCI) and the correlation between multiple influencing factors.Materials and methodsThe sample was comprised of 1325 relatively healthy participants aged ≥ 60 years in a Shanghai community-dwelling (557 males and 768 females). Cognitive function was assessed by Mini-Mental State Examination (MMSE). The Instrumental Activities of Daily Living (IADL) scale was used to assess the activities of daily living.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
3
14
1
Order By: Relevance
“…However, current research findings on gender differences in the prevalence and influencing factors of MCI remain inconsistent. Although some studies found no gender difference in the prevalence of MCI, 29–31 other studies found that the prevalence of MCI was higher in females than in males 32,33 . Furthermore, the rate of progression to AD in patients with MCI is higher in females than in males, 34,35 and females with MCI may be more likely to have pre‐dementia.…”
Section: Discussionmentioning
confidence: 97%
“…However, current research findings on gender differences in the prevalence and influencing factors of MCI remain inconsistent. Although some studies found no gender difference in the prevalence of MCI, 29–31 other studies found that the prevalence of MCI was higher in females than in males 32,33 . Furthermore, the rate of progression to AD in patients with MCI is higher in females than in males, 34,35 and females with MCI may be more likely to have pre‐dementia.…”
Section: Discussionmentioning
confidence: 97%
“… 23 Abebe et al 24 assessed cognitive function in patients with BC. The MMSE has been widely applied in cognitive studies of Chinese patients 25 - 27 and its reliability and validity have been verified previously. 28 , 29 MMSE scores ≤26 were considered to indicate cognitive impairment, while scores of 27 to 30 were considered normal.…”
Section: Methodsmentioning
confidence: 95%
“…To our knowledge, no studies have focused on the association between lifestyle and genetic risk ( APOE and MTHFR ) in the development of MCI, and most have focused on single lifestyle factors or the APOE gene instead of combined factors . A cross-sectional study of Chinese adults aged 80 years or older showed that healthy lifestyle was associated with better cognitive function in older adults, regardless of APOE genotype .…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of evidence that individuals who have healthy diets, get regular physical activity, limit alcohol consumption, and do not smoke can reduce their risk of MCI . Some studies have combined lifestyle factors into healthy lifestyle scores to investigate their association with other diseases, such as dementia and cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%